Countering Campus Extremism in Southeast Asia - Welch, Anthony (International Higher Education, 2015)
While extremism has long been a problem in higher education, the rise of militant Islam is proving a challenge for many countries, including several Muslim nations. Campus radicalism in South East Asia, most notably Malaysia and Indonesia, has led to campaigns to counter campus extremism, although their effectiveness is not clear. Ongoing recruitment by Islamists on campus remains a problem.